European Consultation-Liaison Psychiatric Services: the ECLW Collaborative Study - Huyse, F (2012)
OBJECTIVE: To describe the patterns of organization of consultation-liaison (C-L) services in 11 European countries in relation to hospital characteristics and national approaches to C-L psychiatry. METHOD: Cross-sectional survey. RESULTS: Services can best be described in terms of their size and seniority of their staff and whether or not they are multidisciplinary. Single-discipline services are based upon the standard medical consultant model, whereas those with multidisciplinary teams work in a way that is comparable with community mental health teams. German psychosomatic C-L services belonged to either model. National differences were found. CONCLUSION: This first international study provides empirical evidence for the wide variation in the organization of C-L services. In view of the increasing numbers of patients with psychiatric disorder who are being treated in general hospitals and the changing patterns of medical care there are important implications for clarification and improvement of the role of C-L services.